Local wisdom regarding coastal resource management among a fishermen community in Youtefa Bay, Papua. - Kadir, Akhmad; Poli, Agustina Ivonne; Hijjang, Pawennari; idris, usman; Ali, Aisyah; Sokoy, Fredrik (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
One model of ownership of access and the management of coastal and marine resources is a communal property widely applied to indigenous peoples who have ”hak ulayat” (customary rights) over coastal and marine areas. This article aims to analyze and deeply describe the traditional knowledge systems and coastal resource management of the Tobati-Enggros coastal fishermen. This research is a qualitative descriptive study using an ethnographic approach. The data collection techniques used were in-depth interviews and field observations. The data analysis is interpretive descriptive. The results showed the traditional maritime knowledge system in Tobati-Enggros fishers includes the nature of the marine coast, fishing gears, types of fishing, and fishing season. Management of Coastal Resources is also regulated in the Customary Authority under the leadership of ”Keondoafian” (tribal chief) by implementing Manjo in managing coastal resources. This shows that the existence of Manjo customary law and subsistence utilization patterns, based on traditional knowledge systems, the Tobati-Enggros fishing community has local wisdom values closely connected with the aim of marine conservation.